Study of Erythropoietin and number of antibiotics in renal failure and thalassemia patients - Ansam Hussein Ali; Sahib J. Abdurahman; Mousa J. Mohammed (Tikrit Journal of Pure Science)
The current study included 130 people over a period of research from October 2015 to May 2016 who have renal failure and thalassemia. Samples were studied divided in three groups: the first group: included 50 people (62-20 years) with renal failure, and the second group: included 50 people(30-12 years) infected with thalassemia in addition to the 30 people (18-54 years) represented a group of healthy control. The present study aimed to find out the dynamic effect of the hormone erythropoietin and its role in anemia by examining the level of serum hormone erythropoietin among patients with thalassemia as well as anemia in patients with renal failure, in addition to the effect of some of the biochemical parameters associated antioxidants system such as Glutathione (GSH), superoxide dismutase (SOD) and catalase. The study concludes the following results: The results showed a significant decrease (P≤0.01) in the concentration of the erythropoietin hormone in the two groups of patients renal failure  while there was a significant increase in patients with a group of thalassemia for males and did not record results significant difference for a group of female thalassemia patients when compared with the control group. The results show that there is a significant decrease in the level of glutathione and SOD and catalase enzyme, and for both males and females in the patients groups when compared with the control group